Altered pain sensitivity in elderly women with chronic neck pain - Sureeporn Uthaikhup (2018)
© 2015 Uthaikhup et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in anymedium, provided the original author and source are credited. Background Age-related changes occur in both the peripheral and central nervous system, yet little is known about the influence of chronic pain on pain sensitivity in older persons. The aim of this study was to investigate pain sensitivity in elders with chronic neck pain compared to healthy elders. Methods Thirty elderly women with chronic neck pain and 30 controls were recruited. Measures of pain sensitivity included pressure pain thresholds, heat/cold pain thresholds and supra-threshold heat pain responses. The pain measures were assessed over the cervical spine and at a remote site, the tibialis anterior muscle. Results Elders with chronic neck pain had lower pressure pain threshold over the articular pillar of C5-C6 and decreased cold pain thresholds over the cervical spine and tibialis anterior muscle when compared with controls (p < 0.05). There were no between group differences in heat pain thresholds and supra-threshold heat pain responses (p > 0.05). Conclusion The presence of pain hypersensitivity in elderly women with chronic neck pain appears to be dependent on types of painful stimuli. This may reflect changes in the peripheral and central nervous system with age.